2010
DOI: 10.1242/jcs.061010
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 and Fbw7 cooperate to induce p63 protein degradation following DNA damage and cell differentiation

Abstract: SummaryTight control of p63 protein levels must be achieved under differentiation or apoptotic conditions. Here, we describe a new regulatory pathway for the Np63 protein. We found that MDM2 binds Np63 in the nucleus promoting its translocation to the cytoplasm. The MDM2 nuclear localization signal is required for Np63 nuclear export and subsequent degradation, whereas the MDM2 ringfinger domain is dispensable. Once exported to the cytoplasm by MDM2, p63 is targeted for degradation by the Fbw7 E3-ubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 50 publications
5
97
1
Order By: Relevance
“…Because of key roles of p63 in cell growth and proliferation, apoptosis and differentiation, p63 levels are tightly regulated, mainly by the ubiquitin-dependent proteasomal degradation pathway (38). Recent studies have shown that degradation of p63 during KC differentiation by E3 ubiquitin ligase requires GSK3 kinase activity (39). Given that GSK3 is a potential substrate for PKD signaling (40), it is tempting to speculate that PKD3 signaling may stabilize p63 in proliferative KCs through negative regulation of GSK3.…”
Section: Discussionmentioning
confidence: 99%
“…Because of key roles of p63 in cell growth and proliferation, apoptosis and differentiation, p63 levels are tightly regulated, mainly by the ubiquitin-dependent proteasomal degradation pathway (38). Recent studies have shown that degradation of p63 during KC differentiation by E3 ubiquitin ligase requires GSK3 kinase activity (39). Given that GSK3 is a potential substrate for PKD signaling (40), it is tempting to speculate that PKD3 signaling may stabilize p63 in proliferative KCs through negative regulation of GSK3.…”
Section: Discussionmentioning
confidence: 99%
“…In response to several genotoxic agents, ubiquitylation and proteasomal degradation were shown to be prevented by phosphorylation on the TA isoforms (Rossi et al, 2006;Li et al, 2008;MacPartlin et al, 2008), whereas promoted also, by phosphorylation on the DN isoforms (Liefer et al, 2000;Westfall et al, 2005; HIPK2/DNp63a axis in DNA damage response C Lazzari et al Zangen et al, 2005). Though Y phosphorylation was overall shown to be associated to TA stability (Gonfloni et al, 2009;Wang et al, 2010) and S/T phosphorylation to DN degradation (Westfall et al, 2005;Huang et al, 2008;Galli et al, 2010), the molecular pathways underlying these divergent events and their balance have just begun to be described. The HIPK2 activity on DNp63a we are reporting here is consistent with the general idea that the cellular amount of this p63 isoform has to be reduced to enable an effective DDR.…”
Section: Discussionmentioning
confidence: 99%
“…A strong functional link between DNp63a phosphorylation and its subsequent degradation has been observed upon treatment with different genotoxic agents (Papoutsaki et al, 2005;Westfall et al, 2005;Huang et al, 2008;Galli et al, 2010). In addition, upon CDDP treatment, three specific phosphorylation sites (that is, S375, T397 and S466) have been identified in the C-terminal region of DNp63a by mass spectrometry (Huang et al, 2008; Figure 5c, underscored sites).…”
Section: Hipk2 Contributes To Tumor Cell Chemosensitivity Through P53mentioning
confidence: 93%
“…On the contrary, Calabro et al [54] showed that p63α and p63γ are able to associate with human Mdm2, and that Mdm2 is able to increase the steady-state level of p63 and enhance transcriptional activity under conditions in which p53 is inhibited. Most recently, Galli et al [55] have shown that Mdm2 induces p63 protein degradation following DNA damage and cell differentiation. They demonstrated that Mdm2 binds ΔNp63α in the nucleus, promoting its translocation to the cytoplasm, where it is targeted for degradation.…”
Section: Tp63 Gene and P63 Protein Isoformsmentioning
confidence: 99%